Women performing aarti of the Mukhalingam - Mumbai Archive Project Team (Jio Institute, 2024)
The palki stops in front of the household where the women perform aarti of the mukhalingam with a diya (lamp with wicks soaked in ghee or oil) or camphor, which burns without leaving a residue. Kumkum (vermilion) and chandan (sandalwood paste) are used for applying tilak (a mark) to the forehead of the deity as a sign of blessing and protection.